2016
DOI: 10.1016/j.jglr.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Brackish-water residency and semi-anadromy in Arctic lake trout (Salvelinus namaycush) inferred from otolith microchemistry

Abstract: Lake trout, Salvelinus namaycush, are considered a freshwater species but have been documented using brackish and marine water environments in the Arctic in a semi-anadromous manner. The objective of this study was to describe lake trout life histories present in the brackish waters of Husky Lakes, Northwest Territories (NT) using otolith strontium (Sr) profiles obtained by Laser Ablation Inductively-Coupled Plasma Mass Spectrometry (LA-ICP-MS). Lake trout from Husky Lakes and Noell Lake (freshwater), NT were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
(95 reference statements)
0
18
1
Order By: Relevance
“…Stream spawning by lake trout also occurs in select tributaries of lakes Nipigon and Superior (Dymond, ; Loftus, ). Recently, populations of lake trout were identified that exclusively spawn and reside in brackish‐water drainage basins (1–11 psu) of the coastal Canadian Arctic (Kissinger et al., , ).…”
Section: Interspecific Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stream spawning by lake trout also occurs in select tributaries of lakes Nipigon and Superior (Dymond, ; Loftus, ). Recently, populations of lake trout were identified that exclusively spawn and reside in brackish‐water drainage basins (1–11 psu) of the coastal Canadian Arctic (Kissinger et al., , ).…”
Section: Interspecific Comparisonsmentioning
confidence: 99%
“…Arctic charr and lake trout predominantly follow a fully lake‐resident life history, but there are instances of other life‐history types and lake‐rearing strategies (Kissinger et al., ; Klemetsen et al., ). Entirely fluvial populations of Arctic charr occur in isolated stream systems (McCart, ), but we found no such examples in lake trout.…”
Section: Interspecific Comparisonsmentioning
confidence: 99%
“…Lake trout are considered a freshwater species (Scott and Crossman, 1973), but have been documented to undertake occasional migrations to brackish water environments in Western Arctic areas (Harwood et al, 2008;Swanson et al, 2010). Results from otolith strontium analyses indicated that the majority (e.g., 85%) of lake trout from Husky Lakes spawn and spend their entire lives in brackish waters (Kissinger et al, 2015). Herein, species-environment correlations indicate that increasing salinity was clearly a limiting factor to lake trout abundance and distribution in Husky Lakes.…”
Section: Fish Assemblage Structure and Environmental Gradientsmentioning
confidence: 99%
“…The Arctic guild comprises fish species with limited distribution and/or narrow physiological ranges that are particularly sensitive to changing environmental conditions (Roessig et al, 2004;Reist et al, 2006;Pörtner and Peck, 2010). On the other hand, several Arctic fishes exhibit complex life histories enabling them to occupy a variety of habitats and take advantage of patchy and highly seasonal resources (Craig, 1984;Power, 1997;Tallman et al, 2002;Reshetnikov, 2004;Kissinger et al, 2015). Estuarine fish communities integrate environmental information from marine, freshwater and terrestrial (catchment) environments (Khlebovich, 1997;Whitfield and Harrison, 2008), and are thus excellent candidates for monitoring environmental change (Whitfield and Elliot, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In estuaries, salinity often has a positive correlation with otolith Sr:Ca when the freshwater end-member has lower Sr:Ca than sea-water (Secor, Rooker, 2000;Kraus, Secor, 2004;Martin et al, 2004;Sturrock et al, 2012). The techniques used to study ontogenetic changes of Sr:Ca ratio in otoliths include spot and line scan analysis by electron probe microanalysis (EPMA), microproton-induced X-ray emission (micro-PIXE) (Lin et al, 2007;Hedger et al, 2008;Daros et al, 2016), and more recently laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) (MoralesNin et al, 2014;Fowler et al, 2016;Kissinger et al, 2016;Avigliano et al, 2017b;Callicó Fortunato et al, 2017).…”
Section: Introductionmentioning
confidence: 99%